ANALISIS TAX PLANNING DALAM UPAYA MENINGKATKAN OPTIMALISASI PEMBAYARAN PAJAK PENGHASILAN PADA PT.CHIDEHAFU - Natakharisma, Vyakana; Sumadi, I Kadek (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
Income tax is a tax imposed on any additional economic benefit derived by the taxpayer can be used to increase the wealth of the taxpayer . In terms of taxpayer to pay taxes usually strives to optimize its tax burden can be achieved through tax planning . This study aims to determine the optimization efforts to increase income tax payments can be made by PT.Chidehafu through tax planning and tax planning impacts on the payment of income tax section 21 and corporate income tax of PT.Chidehafu . The analysis technique used is descriptive qualitative analysis . Based on the analysis, after tax planning with net method PT.Chidehafu will pay income tax more Rp 156.303 , 00 than before tax planning . However, with gross-up method PT.Chidehafu can save income tax payments for Rp 1.462.070 , 00 .
Keywords: tax planning; income tax; optimalization